GRA Z GATUNKIEM JAKO SPOSÓB PRZEZWYCIĘŻENIA KRYZYSU TRADYCYJNYCH FORM W LITERATURZE BIAŁORUSKIEJ (NA PODSTAWIE DZIENNIKA FACEBOOKOWEGO RADZIWA „PRUDOK” ANDRUSIA HORWATA) - Raspapou, Aliaksandr (Acta Neophilologica, 2019)
In this article, I analyze the problem of the interaction between literary and paralit-erary genres in the work of the Belarusian writer Andrus Horvat, winner of the Maxim Bahdanovich “Debut” Award in 2017. The intermedial potential, especially genealogical features of his work Radziwa ‘Prudok’ [‘Prudok’ Radio Station] will be discussed, as well as how it operates within the context of literature and various forms of visual art, which are subsumed under the main theme of this work, i.e. the search for the lost identity by the young generation of Belarusians.